Pengembangan Media KIncir Pintar dengan Metode Demonstrasi dan Bermain untuk meningkatkan kemampuan Bahasa Ekspresif dan keaksaraan Anak Usia 5-6 Tahun di TK Negeri Pembina Batang - Herowati, Eny; Dwijayanti, Ida; Buchori, Achmad (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
The background of this research is the conditions in the Batang Pembina Batang State Kindergarten, Kalisalak Village, Batang. Researchers also found problems learning expressive language skills and expressive language literacy and low literacy reaching 75%. The approach used in this research is the type of research carried out is the ADDIE development research method including: Analysis, Design, Development or Production, Implementationor Delivery and Evaluations. The ADDIE model was developed by Dick and Carry in 1996 to design learning systems (Mulyaningsih, 2016). This model can be used for various forms of product development in learning activities such as models, learning strategies, learning methods, media and teaching materials. The results of this study are 1. Results of the Smart Wheel (Kintar) media validation using demonstration and play methods to improve expressive language skills and literacy of children aged 5-6 years with very valid criteria. 2. Practicality The validation of the Smart Wheel (Kintar) media with the demonstration and playing method developed can improve expressive language skills and early childhood literacy in kindergarten based on the results of teacher and student response questionnaires. 3. Being able to improve the expressive language skills and literacy of children aged 5-6 years in Kindergarten. The effectiveness of learning using the Smart Wheel (Kintar) media with demonstration and play methods can be seen through the effectiveness test with the result that the Smart Wheel (Kintar) media with Demonstration and play methods can improve expressive language skills and motor literacy in early childhood in kindergarten, this is shown by the average score of students' learning ability assessment of 4.00. it can be concluded that the effectiveness of the Smart Wheel (Kintar) media with demonstration and play methods to improve expressive language skills and early childhood literacy falls within the very good criteria.